2007
DOI: 10.3354/meps07223
|View full text |Cite
|
Sign up to set email alerts
|

Computation of primary production from remote sensing of ocean colour at the northwestern Atlantic C-SOLAS Lagrangian site

Abstract: At the C-SOLAS Lagrangian Study site, the phytoplankton community was dominated by diatoms in declining bloom conditions, which were characterised by a decrease in primary production over time. Measurements of primary production were performed using photosynthesis-light experiments and simulated in situ incubations. Several methods were used to assign photosynthetic parameters for estimation of primary production from remote-sensing of ocean colour: (1) the nearestneighbour method (NNM), (2) a temperature-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…The corresponding respiration rate, assumed to be constant throughout the day, is estimated to be 0.05 µmol C (l h) −1 ; the rates of NCP and GPP are 0.26 µmol C (l h) −1 and 0.31 µmol C (l h) −1 , respectively, both lasting approximately 10 h per day. This compares well with the GPP estimates given by Forget et al (2007, their Table 2), which, when combined with an assumed 30 m MLD, yield GPP rates of 13 µmol C (l d) −1 . It must be noted, however, that their station is somewhat further offshore at the shelf break than the mooring location of the CARIOCA buoy and the SeaHorse.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The corresponding respiration rate, assumed to be constant throughout the day, is estimated to be 0.05 µmol C (l h) −1 ; the rates of NCP and GPP are 0.26 µmol C (l h) −1 and 0.31 µmol C (l h) −1 , respectively, both lasting approximately 10 h per day. This compares well with the GPP estimates given by Forget et al (2007, their Table 2), which, when combined with an assumed 30 m MLD, yield GPP rates of 13 µmol C (l d) −1 . It must be noted, however, that their station is somewhat further offshore at the shelf break than the mooring location of the CARIOCA buoy and the SeaHorse.…”
Section: Resultssupporting
confidence: 75%
“…4d). Again, this compares well with the GPP rates of 1-3 µmol C (l d) −1 as reported by Forget et al (2007) for this period. Charette et al (2001) reported 14 C-based GPP rates, determined for the area in September 1997, of 0.9-13 µmol C (l d) −1 , assuming a 30 m MLD.…”
Section: Resultssupporting
confidence: 72%
“…3500 m; Fig. 1) as part of a Lagrangian survey of the decline of the spring bloom in the northwest Atlantic Ocean (Forget et al 2007a). A water mass within which a phytoplankton bloom had developed was sampled from 25 April (Day 1) to 1 May 2003 (Day 7).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Forget et al . [] found a decrease in the photosynthetic parameters during the declining phase of the phytoplankton bloom in the northwestern Atlantic. Although the values of α B at Stns.…”
Section: Discussionmentioning
confidence: 99%